2000
DOI: 10.1108/03090590010373334
|View full text |Cite
|
Sign up to set email alerts
|

Management development issues for owners/managers of micro‐enterprises

Abstract: Management development has traditionally been perceived as being the domain of large rather than micro‐enterprises, with developmental issues normally being addressed by means of educational interventions.However, the challenges and obstacles for growth facing these micro‐enterprises (businesses employing ten people or fewer) differ significantly from those of a larger organisation. Reports on the current provision for management development as it relates to micro‐enterprises, and the perception of owners/mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 11 publications
1
57
0
Order By: Relevance
“…Hypothesis 2: Supports that, as there is positive relationship among market information processing activities (acquisition, dissemination and utilization and product innovation success indicators (financial success and market success) [72]. This finding is consistent with past findings that market information processing activities could affects the success in product innovative at three different levels: project level (e.g., time, cost efficiency and functional success), product level (e.g., profitability, market share and revenues of the new product) and firm level (returns to the firm generated by the new product) suggested that stronger market information processing of a firm is reflected in a higher innovation success (such as both market and financial success).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothesis 2: Supports that, as there is positive relationship among market information processing activities (acquisition, dissemination and utilization and product innovation success indicators (financial success and market success) [72]. This finding is consistent with past findings that market information processing activities could affects the success in product innovative at three different levels: project level (e.g., time, cost efficiency and functional success), product level (e.g., profitability, market share and revenues of the new product) and firm level (returns to the firm generated by the new product) suggested that stronger market information processing of a firm is reflected in a higher innovation success (such as both market and financial success).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of externally created innovation is argued to limit the owner/manager's potential regarding innovation, and such needs are met with relatively conservative responses in the interviewee firms. The direct contact between the owner/manager and the market in day-to-day operations of the firms provides an opportunity to articulate change and innovation, through direct sensing of the market (O'Dwyer and Ryan, 2000). In many of the firms sampled, the owner/managers exhibit an awareness of the market (Camison and Montfort-Mir, 2012) and some interviewees provide evidence supporting the opportunity to differentiate the firm from competitors through levels of guest interaction and yet each appear limited in terms of developing techniques to perform market analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The informality discussed above is also manifest as a lack of formal planning structures (Greenbank, 2000) and by a lack of desire to engage with management development which may mask relatively sophisticated managerial capabilities which are context specific (Devins et al, 2005). In context this informality is often perfectly rational behaviour given that costs of developing new marketing and management systems are both risky and expensive (Cyr et al, 2011) and often unsuitable for the microfirm context (O'Dwyer and Ryan, 2000;Reinl and Kelliher, 2010).…”
Section: Business Philosophymentioning
confidence: 99%
See 2 more Smart Citations